1993
DOI: 10.1002/1097-0142(19930801)72:3<663::aid-cncr2820720307>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of continuous infusion 5-fluorouracil and leucovorin with weekly cisplatin in metastatic colorectal carcinoma

Abstract: Background. Prolonged infusional 5‐fluorouracil (5‐FU) and bolus 5‐FU modulated by leucovorin are associated with higher response rates than bolus 5‐FU alone. Cisplatin enhances 5‐FU cytotoxicity in some preclinical models. Methods. The authors tested the feasibility of combining concurrent infusional leucovorin (500 mg/m2/d) with protracted infusional 5‐FU (200 mg/m2/d) and weekly bolus cisplatin (20 mg/m2) in 22 patients with metastatic colorectal cancer. Results. Four partial responses (PR) were noticed amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Oxaliplatin has a much more potent anticolorectal cancer effect than cisplatin (Grem et al, 1993;de Gramont et al, 2000). However, the molecular mechanism(s) that cause the difference in the effect has not been made clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxaliplatin has a much more potent anticolorectal cancer effect than cisplatin (Grem et al, 1993;de Gramont et al, 2000). However, the molecular mechanism(s) that cause the difference in the effect has not been made clear.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of cisplatin on colorectal cancer is weak. Loehrer et al (1988) and Grem et al (1993) reported rates of response of colorectal cancer to cisplatin-based chemotherapy of 22 and 19%, respectively. On the other hand, for oxaliplatin-based chemotherapy, de Gramont et al (2000) reported that the response rate was 50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is metabolized to its active form 5-fluoruracil (5-FU) by the enzyme thymidine phosphorylase, which exists in higher concentrations in tumor tissue and liver than in normal tissues. 5-FU has been associated with megaloblastic changes, likely secondary to DNA-directed toxicity (Grem et al, 1993). There has been some studies showing the effect of MCV increase on prognosis in patients with metastatic breast cancer treated with Capecitabine (Arslan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the efficiency of cisplatin is generally low in colorectal cancer, with <20% clinical responses when used alone or in combination with 5-fluorouracil or etoposide (3,4). Oxaliplatin is a third-generation platinum coordination complex of the 1,2-diaminocyclohexane families, having been developed after cisplatin and carboplatin (5,6).…”
Section: Introductionmentioning
confidence: 99%